Ineffectiveness of The Legislative Function By The Regional Representative Council (Case Study Of Kebumen Regency) - Utami, Wiji Nurfi; Ardhanariswari, Riris (Trunojoyo Madura University, 2024)
Regional Regulations are an instrument for administering regional government formed by the Regional Legislative Institutions and the Regional Government. Regional Legislative Institutions has the right to submit the Initiative Regional Regulation Draft to the head of Regional Legislative Institutions consists of explanation and Principal Number. The Draft was given Bapemperda to review. The results are reported to the head of Regional Legislative Institutions to be presented at the Plenary Meeting. The Regent and Regional Legislative Institutions discussing Regional Regulations. The formation of legal products is mandate of Act Numb. 12 of 2011 jo. 13 of 2022 about the Legislation Development and Numb. 80 of 2015 jo. Numb. 120 of 2018 about the Regional Legislation. The issues that will be discussed are the process of submitting Initiative Regional Regulation Draft and the problem. The research method is qualitative using a normative juridical and empirical juridical approach. The research location was carried out within the Kebumen Regional Legislative Institutions and Kebumen Regency Legal Section. The results of the research show that there is a need for Regulation that specifically about Initiative Regional Regulation Draft.